UKRAINE'S SHALE BEARING STRATA GAS: GEOCHEMICAL FEATURES - Zagnitko, V.; Mykhailov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Relevance of research is caused by the need to expand the mineral and resource base of fuel and energy resources in Ukraine. The increasing demand for oil and natural gas, depletion of traditional deposits and rising prices cause the considerable interest in the search for hydrocarbon deposits of unconventional type, therefore the interest in studying of various aspects of oil and gas potential of shale strata of Ukraine is growing every year. An important argument in the development of search criteria and evaluation of unconventional hydrocarbon deposits is the study of their component composition and geochemical features. Among the natural gases of gas-bearing shale strata are often present: methane, nitrogen, carbon dioxide, heavy hydrocarbons (ethane, propane, pentane, hexane, butane), hydrogen, hydrogen sulfide, inert gases, and (very rarely) oxides of carbon, nitrogen, sulfur and others. The most common gas components are: methane, nitrogen, carbon dioxide and hydrogen. Formation of gases is associated with the geological history of the formation of separate areas. Therefore their genesis in different periods may be associated with both metamorphism of organic-containing strata, including coal strata, and with deep updrafts, resulting from endogenous causes (mainly due to the dynamics of tectonic development and differentiation of the Earth's geospheres), as well as provoked by external factors (including the fall of large celestial bodies). According to the pyrolysis of samples of shales and other compacted rocks the component composition of gases is defined as very uneven and is difficult to systematize and excretion patterns. In particular, due to the results of these analyzes we can state predominance of carbon dioxide and hydrogen in gases in almost all samples regardless of the lithology composition of host rocks. Some samples recorded high content of sulfurous gases, usually in rocks containing sulfides. Generally, methane content in the samples is less dependent on the content of it in the sequence, particularly in the mineral component of collectors it is also not high. The isotopic composition of carbon in the organic component of the samples is slightly enriched in the heavy isotope 13 (13С = -22 -24‰) and some carbonates contain abnormal amounts of this isotope (13С до +15‰). For the formation of carbonates with this unusual isotopic composition are required unusual physical and chemical conditions of formation, in particular unbalanced conditions of isotopic fractionation resulting in systems supersaturated by hydrocarbons.
Keywords: organic matter; methane; nitrogen; carbon dioxide; Dnieper-Donets depression